2020
DOI: 10.3390/pathogens9110959
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Mycobacterium kansasii Infection in Two Related Cats

Abstract: Mycobacterial infections are a major concern in veterinary medicine because of the difficulty achieving an etiological diagnosis, the challenges and concerns of treatment, and the potential zoonotic risk. Mycobacterium kansasii, a slow-growing non-tuberculous mycobacteria, causes disease in both humans and animals. While infections have been well described in humans, where it may be misdiagnosed as tuberculosis, there are fewer reports in animals. Only four cases have been reported in the domestic cat. This ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 90 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…[1][2][3][4]9 Interestingly, in the cat with vertebral lesions associated with M. kansasii previously reported in the literature, remission of clinical signs was achieved and resolution of the osteolytic lesions was documented 4 months after starting antimycobacterial treatment. 11 Overall, the prognosis in our case was considered guarded. Additionally, there were concerns about the need for prolonged antibiotic therapy, 3,9 with the inherent risk of toxicity and the necessity for owners and patient compliance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[1][2][3][4]9 Interestingly, in the cat with vertebral lesions associated with M. kansasii previously reported in the literature, remission of clinical signs was achieved and resolution of the osteolytic lesions was documented 4 months after starting antimycobacterial treatment. 11 Overall, the prognosis in our case was considered guarded. Additionally, there were concerns about the need for prolonged antibiotic therapy, 3,9 with the inherent risk of toxicity and the necessity for owners and patient compliance.…”
Section: Discussionmentioning
confidence: 63%
“…To the authors’ knowledge, an intradural‐extramedullary granuloma has not been previously reported in cats infected with M. microti . Spinal mycobacteriosis associated with two species of NTM ( M. avium and M. kansasii ) in cats has been reported 10,11 . The cat diagnosed with M. kansasii had a mass lesion causing osteolytic changes at the level of the caudal vertebral bodies 11 ; detailed clinical information about the spinal lesions associated with M. avium has not yet been published 10 …”
Section: Discussionmentioning
confidence: 99%
“…Positive antibody responses to MPB83 have been reported in cats, but the performance for M. microti-infected cats was poor compared to those infected with M. bovis (Rhodes et al, 2011). It is also possible that NTM could incite responses to this major mycobacterial protein, such as M. kansasii, which has been reported in cats (Lee et al, 2017, Černá et al, 2020, Fukano et al, 2021, and so the concern for single-antigen testing in cats is the potential misdiagnosis of this infection as TB.…”
Section: Discussionmentioning
confidence: 99%
“…M. kansasii has been isolated from a wide variety of animals; dogs ( Canis familiaris ), Rhesus Macaque ( Macaca mulatta ) and cats ( Felis catus ) [ 11–14 ]. To our knowledge, three cases of MKC infetion in cat were reported previously [ 12 , 14 ]. All the three cats were presented with cutaneous and systemic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, the cat was treated with trimethoprim-sulphamethoxazole and doxycycline, but it was unsuccessful [ 12 ]. Other two cats were sibling, indoor-only cats and treated successfully with rifampicin, azithromycin and pradofloxacin [ 14 ]. In these cases, commercial identification kit or PCR sequence analysis using partial house keeping genes were performed for bacterial identification.…”
Section: Discussionmentioning
confidence: 99%